Planning of Da'wah Nahdlatul Ulama in Tackling Online Gambling Behavior in the Muslim Community of Batang Toru District, South Tapanuli Regency - Nasution, Muhammad Asnawi; Siregar, Muhammad Habibi (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
Nahdlatul Ulama (NU) is one of the Islamic organizations in Indonesia. In the current digital era, with the advancement of communication technology, especially in the field of smartphone technology, it has provided many conveniences that are useful in life, but on the other hand, it has also provided many disadvantages. The purpose of this discussion is to plan Nahdlatul Ulama (NU) da'wah efforts in addressing online gambling behavior within the Batang Toru District community. This research is included in the type of qualitative descriptive research. The results of the study show that, in the context of da'wah, the strategies developed to eradicate online gambling are varied. Therefore, serious thinking and movement are needed for da'i to anticipate the onslaught of online gambling sites and activities. Because of the complexity of the causes of the spread of online gambling, its eradication also requires a planned and organized strategy. The first step in planning da'wah is to recognize the real conditions of society. For suggestions, NU can conduct a needs assessment through a participatory approach, such as community discussions, local surveys, and in-depth interviews with community leaders. With accurate data, da'wah planning can be arranged contextually.